2009
DOI: 10.1007/s10103-009-0655-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical diagnosis of fissure caries with conventional and laser-induced fluorescence techniques

Abstract: We studied the in vivo validity of dentinal fissure caries diagnosis by visual examination, bitewing radiography, and use of a laser-induced fluorescence device (DIAGNOdent). A total of 144 and second molars with macroscopically intact occlusal surfaces in 41 Chinese young adults were examined visually, by bitewing radiography, and by DIAGNOdent. Visual examination after pit and fissure opening was used as the reference standard. The sensitivity and specificity of detecting caries that had extended into the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
52
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 25 publications
4
52
0
2
Order By: Relevance
“…The LF device had provided results than the radiographic method according to the assessment of sensitivity, specificity, accuracy, AUC, and likelihood ratio values. (12,21,22,27 or various other reasons. The radiographic method and the LF device supplied more diagnostic information than the visual method.…”
Section: Discussionmentioning
confidence: 99%
“…The LF device had provided results than the radiographic method according to the assessment of sensitivity, specificity, accuracy, AUC, and likelihood ratio values. (12,21,22,27 or various other reasons. The radiographic method and the LF device supplied more diagnostic information than the visual method.…”
Section: Discussionmentioning
confidence: 99%
“…6 Other investigators have reported PlgAChi NPs to be safe even at much higher concentrations of 20 mg/ml. [33][34][35] In addition, other research groups revealed interesting cytotoxicity results of chitosan NPs effect on human skin keratinocytes HaCaT cells. Tretinoin containing chitosan solid lipid NPs were not cytotoxic to HaCaT cells even at the highest concentration 500 μg/ml used, which led to around 5 % less viability compared with the control.…”
Section: Original Articlesmentioning
confidence: 99%
“…13 Later on, some other researchers mainly focused on detection of occlusal secondary caries and caries around amalgam restoration margins. [14][15][16] Considering the importance of detecting secondary caries adjacent to composite restorations in the proximal areas (particularly in the gingival floor), the current study focused on this particular area. To the best of our knowledge, similar previous studies focusing on this topic are scarce.…”
Section: In Vitro Comparison Of Diagnostic Accuracy Of Diagnodent Andmentioning
confidence: 99%